2009
DOI: 10.3732/ajb.0800381
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic diversification of Equisetum (Equisetales) as inferred from Lower Cretaceous species of British Columbia, Canada

Abstract: Three types of anatomically preserved vegetative shoots with features that characterize crown group Equisetum have been discovered in Lower Cretaceous deposits (≈136 Ma) of British Columbia, Canada, suggesting the genus is much older than currently believed. Specimens include two types of aerial shoots described as E. haukeanum sp. nov. and E. vancouverense sp. nov. and one type of subterranean rhizome. Shoots are 1-2 mm in diameter, jointed, and in cross section have fluted stems with a hollow pith. Distincti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
28
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 33 publications
2
28
0
Order By: Relevance
“…Equisetum thermale possesses all the general vegetative features that define the family Equisetaceae, including herbaceous, jointed, aerial, and subterranean stems, with numerous wiry roots, and very thin leaves with a single vein borne in whorls and joined in a sheath (e.g., Stanich et al, 2009). Growth in the plant was exclusively primary, and it has vascular anastomosis typical of the family (e.g., Stewart and Rothwell, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Equisetum thermale possesses all the general vegetative features that define the family Equisetaceae, including herbaceous, jointed, aerial, and subterranean stems, with numerous wiry roots, and very thin leaves with a single vein borne in whorls and joined in a sheath (e.g., Stanich et al, 2009). Growth in the plant was exclusively primary, and it has vascular anastomosis typical of the family (e.g., Stewart and Rothwell, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The strobili conform in organization to those of Equisetaceae in that they lack subtending bracts between sporangiophores. Features that differentiate the Equisetaceae from other sphenophytes are tabulated in Stanich et al (2009, Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences between the latter two genera have been extensively discussed (e.g., Harris, 1961;Gould, 1968;Stanich et al, 2009), and many of their representatives have been suggested to belong to the same evolutionary lineage leading to the extant horsetails (Boureau, 1964;Gould, 1968).…”
Section: Fossil Representatives Of Equisetum Have Been Variouslymentioning
confidence: 99%
“…(Early Cretaceous) from the fossil record (Stanich et al, 2009) and possibly extending far back into the Jurassic, since nearly all synapomorphies that define the crown group Equisetum already occur in the anatomically preserved Equisetum thermale Channing, Zamuner, Edwards and Guido, 2011 from the Jurassic of Argentina (see Channing et al, 2011). Nonetheless, a phylogenetic analysis including both living and fossil representatives of the genus is required in order to confirm the position of fossil Equisetum species as part of the crown group, and therefore, the diversification minimum age for that group.…”
Section: Fossil Representatives Of Equisetum Have Been Variouslymentioning
confidence: 99%